Effects and interaction of different interior material treatment and personal preference on psychological and physiological responses in living environment - Sun, Minkai; Nakashima, Taisuke; Yoshimura, Yuri; Honden, Akiyoshi; Nakagawa, Toshinori; Saijo, Hiromi; Watanabe, Yuichiro; Ajimi, Tsuyoshi; Yasunari, Shinji; Yamada, Yuki; Nagano, Jun; Okamoto, Tsuyoshi; et al. (Journal of wood science, 2020)
Japanese cedar ( Cryptomeria japonica ) wood is widely used as a traditional construction material in Japan. The relationship between an individual’s perceived comfort level and a preference for Japanese cedar wood interiors is of interest. We compared volunteers’ physiological responses and subjective evaluations of wooden dwelling spaces with different wood materials: planed Japanese cedar lumber, or printed grain resin sheet overlay boards. Eighty-three subjects were asked to stay in each room for 30 min. We evaluated salivary stress markers, blood pressure, the profile of mood states-brief form (POMS), and a questionnaire that used the semantic differential method to evaluate the subjects’ feeling state for both rooms. The concentrations of the volatile organic compounds in both rooms were also quantified after the experiment. The results demonstrated that the subjects’ evaluation of each room was highly dependent on their preference; each room was evaluated more positively by subjects who preferred it. Although the subjects’ feelings were also influenced by their preference, the room with Japanese cedar did not elicit negative feelings, even from the subjects who disliked it. The subjects’ physiological responses were totally independent of their preferences. Their blood pressure decreased in the Japanese cedar room, and their salivary alpha-amylase activity was repressed in both rooms. These results indicated that the subjective evaluations were influenced in part by the subjects’ preferences, while their physiological responses were not affected. Regardless of which room the subjects preferred, the Japanese cedar room reduced the subjects’ blood pressure compared to the room with artificial materials.